Shaping Strategic Change: The Case of the NHS in the 1980s - Pettigrew, A; Ferlie, E; McKee, L (1992)
This article explores the question of why the management of change has become an issue in the National Health Service (NHS). It reports the results of a study which explored reasons for variability in the observed rate and pace of strategic service change in the NHS. The metaphor of ‘receptive’ and ‘non‐receptive’ contexts for change is introduced and eight ‘signs and symptoms’ of receptivity outlined. Some examples are presented. These results give us a logic and language which may enable us to understand processes of change in the NHS.